2014
DOI: 10.1371/journal.pone.0093959
|View full text |Cite
|
Sign up to set email alerts
|

Merocel versus Nasopore for Nasal Packing: A Meta-Analysis of Randomized Controlled Trials

Abstract: ObjectiveTo compare the clinical outcomes, including efficacy and complications, of Merocel versus Nasopore as a nasal packing material after nasal surgery.MethodsRelevant randomized controlled trials were identified from electronic databases (The Cochrane Library, PubMed, EMBASE, China National Knowledge Infrastructure and Chinese Biomedical Database). Conference proceedings and references from identified trials and review articles were also searched. Outcome measures were pain during nasal packing, pain and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 23 publications
(32 reference statements)
2
58
1
1
Order By: Relevance
“…36 There are various packing materials available, including nonabsorbable packing such as gauze and polyvinyl acetate sponge (Merocel; Medtronic Xomed, Jacksonville, FL) and absorbable packing such as Nasopore (Polyganics, Groningen, the Netherlands) and Sorbsan (Aspen Medical Europe Ltd., Ashby-de-la-Zouch, United Kingdom) (calcium alginate). 37,38 In our study, nasal bleeding and septal hematoma did not differ between the two groups. Nasal packing intended to reduce septal hematoma was not more effective at preventing hematomas compared to transseptal sutures or Silastic splints.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…36 There are various packing materials available, including nonabsorbable packing such as gauze and polyvinyl acetate sponge (Merocel; Medtronic Xomed, Jacksonville, FL) and absorbable packing such as Nasopore (Polyganics, Groningen, the Netherlands) and Sorbsan (Aspen Medical Europe Ltd., Ashby-de-la-Zouch, United Kingdom) (calcium alginate). 37,38 In our study, nasal bleeding and septal hematoma did not differ between the two groups. Nasal packing intended to reduce septal hematoma was not more effective at preventing hematomas compared to transseptal sutures or Silastic splints.…”
Section: Discussioncontrasting
confidence: 42%
“…Nasal packing has been used after septoplasty for the approximation of bilateral mucoperichondrial flaps to minimize bleeding and septal hematoma, to support the neo‐organized septal cartilage and bony fragments, and to prevent synechia and lateral nasal wall movement . There are various packing materials available, including nonabsorbable packing such as gauze and polyvinyl acetate sponge (Merocel; Medtronic Xomed, Jacksonville, FL) and absorbable packing such as Nasopore (Polyganics, Groningen, the Netherlands) and Sorbsan (Aspen Medical Europe Ltd., Ashby‐de‐la‐Zouch, United Kingdom) (calcium alginate) …”
Section: Discussionmentioning
confidence: 99%
“…3,10 In our study, average VAS scores were 5.68 for the control group and 5.56 for the study group and this difference was not statistically significant (P ¼ 0.086) Bleeding incidence following the removal of the merocel pack was found to be 0.12 in the PRP group and 0.50 in the control group. Visual analogue scale score has been used to measure the pain in many studies.…”
Section: Discussionmentioning
confidence: 50%
“…2 Platelet-rich plasma (PRP) has been used in clinics for a long time to take advantage of this condition. 3 Although the positive effects of PRP in the sense of wound recovery have been indicated in many studies, during literature research we have found out that there are few studies with prospective control about the use of PRP in nasal surgery. For example, it is being used in surgical operations (orthopedic operations, maxillofacial attempts, flap shifting operations, etc.…”
mentioning
confidence: 99%
“…Nasal tampons are used to control post-septoplasty bleeding for septum stabilization and to prevent hematoma and adhesion (1)(2)(3). However, nasal tampon application has disadvantages, such as pain, nasal obstruction, nasal mucosal injury, respiratory disorder in sleep, oxidative stress, allergic reactions, dysphagia, eating difficulties, pain and bleeding during removal of the tampon, and toxic shock syndrome (4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%